The Impact of Pedagogical Approaches for Forming Digital Competence in Students - Aigul Medeshova; Nurya Adelbaeva; Alman Kushekkaliev; Saule Akimova; Gulnar Khazhgaliyeva; Lyazzat Ramazanova; Аkmaral Kassymova (Qubahan Academic Journal)
The digital revolution in education has fundamentally transformed teaching methods in higher education. Fostering students' digital competencies is vital for equipping them with the skills needed in our rapidly evolving technological landscape. This article focuses on formulating effective pedagogical strategies and methods for enhancing the digital competence of part-time students. It aims to provide measurable outcomes in terms of students' improved digital skills. The methodology developed combines traditional and digital teaching methods and underscores the teacher's pivotal role in its implementation, clarifying the concept of "digital competence." Employing specific quantitative and empirical research methods, ensures the methodological rigor of this study. The resulting methodology is designed to establish a digital ecosystem within higher education, enabling students to thrive in the digital age and contributing to the broader academic discourse on digital competence.